Barriers to Maternal and Child Health Care Service Uptake in Assosa Zone, Benishangul Gumuz Region, Ethiopia: A Qualitative Study - Mulatu Agajie; Solen Abera; Eshetu Yimer; Gizachew Yaregal; Amir Muhidin; Wagari Kelbessa; Dula Ayana; Debebe Shaweno (Hindawi Limited, 2021)
Background. Ethiopia has reduced maternal mortality from 871 to 412 per 100,000 live births between 2000 and 2016. In 2019, under-5 mortality rates in Ethiopia were 55 deaths per 1,000 live births. Benishangul Gumuz was the second-largest region in the under-5 mortality rate (98/1,000 live births) in the country. Maternal and child health care service uptake is an important indicator of health outcomes. This study is aimed at exploring major barriers to maternal and child health care uptake in Assosa Zone. Methods. This study was conducted in the Bambasi, Menge, and Sherkole districts of the Assosa Zone from July 17 to August 31/2019. The study explored the life experience of study participants about MCH services. The sampling technique was purposive, and data collection methods were focus group discussions, key informant interviews, and in-depth interviews. Data were analyzed thematically. Result. The main barriers to child health care services were financial problems, lack of knowledge, preference of traditional medicines for a sick child, women having no time to care for their sick child, poor roads. poor health facility readiness, the poor economy of families, lack of ambulance, cultural and traditional beliefs, providers being male, and unprofessional behaviors which were the major barriers hindering the uptake of maternal health service utilization. Conclusion. Poor health facility readiness, indirect costs, inaccessibility to health facilities, and cultural and traditional practices were among the major barriers to service uptake identified by this research in the study area.